2017
DOI: 10.1111/1462-2920.13632
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial community collapse: a meta‐analysis of the sinonasal microbiota in chronic rhinosinusitis

Abstract: Chronic rhinosinusitis (CRS) is a common, debilitating condition characterized by long-term inflammation of the nasal cavity and paranasal sinuses. The role of the sinonasal bacteria in CRS is unclear. We conducted a meta-analysis combining and reanalysing published bacterial 16S rRNA sequence data to explore differences in sinonasal bacterial community composition and predicted function between healthy and CRS affected subjects. The results identify the most abundant bacteria across all subjects as Staphyloco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
167
2
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 163 publications
(199 citation statements)
references
References 77 publications
18
167
2
4
Order By: Relevance
“…The role of Corynebacterium within the gut microbiota is not well studied. However, increased abundances of Corynebacterium have been associated with chronic inflammation of the nasal sinus (Abreu et al., ; Wagner Mackenzie et al., ), induced inflammation of the gut (Ribière et al., ) and viral infection in pandas (Zhao et al., ), collectively indicating these bacteria may be associated with inflammatory immune responses. Moreover, Rooks et al.…”
Section: Discussionmentioning
confidence: 99%
“…The role of Corynebacterium within the gut microbiota is not well studied. However, increased abundances of Corynebacterium have been associated with chronic inflammation of the nasal sinus (Abreu et al., ; Wagner Mackenzie et al., ), induced inflammation of the gut (Ribière et al., ) and viral infection in pandas (Zhao et al., ), collectively indicating these bacteria may be associated with inflammatory immune responses. Moreover, Rooks et al.…”
Section: Discussionmentioning
confidence: 99%
“…One such example is chronic rhinosinusitis (CRS), characterized by prolonged inflammation of the sinuses and a shift from a Th1 to a Th2 response (Aurora et al, 2013). Microbial communities in the paranasal sinuses of CRS patients are less rich and less diverse than commensal communities in healthy individuals (Wagner Mackenzie et al, 2017). Linear discriminant analysis identified the genus Corynebacterium as a potential biomarker that was over-represented in CRS.…”
Section: Pathogens As Disturbance: Mechanisms Of Interplay Between Homentioning
confidence: 99%
“…Increased relative abundance and diversity-particularly of Propionibacterium, Burkholderia, and L. sakei-was associated with healthy sinuses. The first two bacteria are also called "gatekeepers" and are thought to play an important role in maintaining a stable sinonasal community [28]. It is important to note that the studies that examined the microbiome in healthy subjects demonstrated the presence of Staphylococcus, Streptococcus, and Pseudomonas, bacteria known to cause respiratory disease [6,7,16].…”
mentioning
confidence: 99%